Comparison between taxane-based chemotherapy with conventional surgery-based therapy for cutaneous angiosarcoma: a single-center experience. (October 2014) - Fujisawa, Yasuhiro; Nakamura, Yasuhiro; Kawachi, Yasuhiro; Otsuka, Fujio
Objective:To show the efficacy of taxane-based chemotherapy for the treatment of cutaneous angiosarcoma. Methods: A case–control study comparing patients who received taxanes without wide local excision (group A, n = 5) and patients who received conventional surgery-based therapy (group B, n = 8) in one university hospital in eastern Japan. Data were collected from a total of 13 patients with cutaneous angiosarcoma treated from November 1997 through July 2009. Results:Group A received taxanes: four patients received docetaxel, and one patient received paclitaxel. Radiation was used concomitantly in two patients. Marginal local excision was performed in two patients. Group B received wide local excision followed by radiation (six patients), docetaxel (three patients), and interleukin-2 (two patients). No patients in group A had local recurrence, whereas five out of the eight patients in group B did (p < 0.05, chi-square test). Median overall survival was 31 months in group A and 10 months in group B. Estimated overall survival using the Kaplan–Meier method was significantly longer in group A (p < 0.05, log-rank test). Conclusion: In our series, taxane-based chemotherapy was superior to conventional surgery-based therapy. Our results indicated that taxane regimens without mutilating surgery offered both local control and prevention of metastasis, which led to prolonged survival.